Bright, stable, and tunable solid-state luminescence of carbon nanodot organogels. Issue 26 (25th June 2018) - Gan, Zhixing; Liu, Lizhe; Wang, Li; Luo, Guangsheng; Mo, Chunlan; Chang, Chenliang
Abstract : Stable, bright, and tunable solid-state luminescence was achieved in carbon nanodots through engineering photon reabsorption. Abstract : Despite the sustained enthusiastic interest in fluorescent carbon nanodots (FCNDs), it is still challenging to achieve bright and widely tunable solid-state luminescence. Herein, organogels embedded with FCNDs were simply synthesized via a one-pot pyrolysis method. Subsequently, the excitation of a single ultraviolet (UV) excitation line results in tunable solid-state luminescence ranging from blue to red with quantum yields (QYs) >14%. In this study, N and S elements were co-doped to regulate the aggregation of FCNDs, which consequently modulated the Stokes shift of the photoluminescence (PL) by managing the degree of photon reabsorption. Notably, without compact aggregations, the dispersions of FCNDs in the organogel matrix indeed render bright fluorescence, which results from the suppression of excessive photon reabsorption and nonradiative resonant energy transfer (NRET).